Business cycles synchronisations in the Baltic countries - Kregždė, Arvydas (Business, Management and Economics Engineering, 2020)
Purpose – The purpose of the paper is to investigate the level of real business cycles synchronisation between the Baltic and the Nordic countries and between the Baltic countries and the euro area. Research methodology – Wavelet analysis was employed to evaluate the level of synchronisation for different periods and time. Quarterly data from 1995 Q2 to 2019 Q4 was used. Findings – We discover the influence of several essential events in economies of the Baltic countries on the synchronisation: accession to the EU in 2004, the introduction of the euro in the Baltic countries and some external shocks. Research limitation – A lack of reliable long-term data from the Baltic countries does not allow performing calculation for other important financial variables. Practical implications – Results of the research are important for forecasting and implementing flexible economic policies of the Baltic countries. Originality/Value – Business cycles synchronisation between the Baltic countries themselves and between the Baltic countries, the Nordic countries and the euro area countries across time and various frequency dimensions was investigated for the first time.